Micelles as Supercages for Bimetallic Nanoparticles Synthesis - C. Tojo; E. Gonzalez; N. Vila-Romeu (Recent Progress in Science and Technology Vol. 2, 2023)
The improvement of the bimetallic nanoparticles characteristics relies on the ability to tune the metal arrangement and surface properties, which requires an advanced control of the synthetic method. We carried out a computer simulation study on the formation of bimetallic nanoparticles by the microemulsion route. A comprehensive analysis of the resulting nanostructures was performed in the light of the influence of intermicellar exchange on reactivity. For a couple of metals whose difference in standard reduction potentials is about 0.2- 0.3 V, and using a quite flexible surfactant, the reaction rate of each metal was monitored versus time using different reactant proportions. It was proved that reaction rates depends not only on the chemical reduction rate but also on intermicellar exchange rate, because the intermicellar exchange plays as dosing pump, which results in an accumulation of slower precursors within micelles, thereby improving the slower chemical reduction. So the slower reduction rate strongly depends on the quantity of reactants in micelles. On the contrary, faster reduction rate is just limited by the intermicellar exchange rate, and no reactants accumulation takes place. This different interplay between both metal reduction rates and the compartmentalization of the reaction media have key repercussions on the sequence of metals reduction. Hence different precursor proportions leads to different sequences of metals reduction, so the arrangement of the two metals in the resulting nanostructure can be manipulated just by changing the precursor proportions.